А comprehensive approach to the diagnosis of crisis status of business entities in a pandemic condition (Economics and region, 2021)
The article actualizes the issue of crisis diagnosis as a basis for timely detection of problems in the activities of business entities. It is substantiated that in the conditions of the COVID-19 pandemic and related quarantine restrictions, there was a significant decline in economic activity of the population, which caused a crisis in many businesses. The impact of the pandemic on the activities and financial condition of enterprises in Ukraine has been studied. A comprehensive approach to assessing the crisis of economic entities, which takes into account the diagnosis of different types of crises based on a system of criteria and allows you to assess the depth of their development. This approach is the basis for the development of timely and adequate measures to combat crisis processes and prevent bankruptcy.
Keywords: crisis state; bankruptcy; pandemic COVID-19; diagnostics